Natural porous nanorods used for high-efficient capture and chemical conversion of CO2. Issue 42 (December 2020) - Wang, Gang; Guo, Ruixiang; Wang, Wenjie; Liu, Weisheng
Graphical abstract: Highlights: For the first time, the natural one-dimensional multifunctional porous nano-mineral attapulgite rod is directly used for CO2 capture and high-efficient conversion. Clever use of the unique polymetallic weak alkaline pore structure of attapulgite effectively captures CO2 effect and promotes the efficient catalytic reaction. The catalytic system had an unusual activity and displayed broader substrate scopes. Combining the unique properties of attapulgite, ZIF-8 was combined with attapulgite in situ for the first time to prepare a highly efficient nanocomposite catalyst with multi-site synergistic catalysis. The catalyst has the advantages of natural raw materials, simple preparation process, low price, and can be recycled. Abstract: There are abundant mineral resources in nature, and how to skilfully use natural mineral resources as a novel material for CO2 capture and conversion seems to be one of the most sensible strategies. Therefore, for the first time, we report a natural and inexpensive nano-mineral as a bifunctional material for CO2 efficient capture and conversion. The material is a natural 1D porous nanomaterial, and its unique multi-metal weak alkaline pore structure, not only can capture CO2, but also has the advantages of multi-metal synergistic catalysis. The best catalytic activity is shown in the coupling reaction of CO2 with epoxy compounds compared to other clay minerals reported. The catalyst has a unique pore structure, which makes it exhibit excellent substrate selectivity in the catalytic reaction and has remarkable catalytic activity for the sterically hindered epoxy substrate. In addition, the nano-catalyst prepared by using attapulgite as a carrier in combination with ZIF-8 exhibits best catalytic activity as compared with the use of any of its components alone. This new type of natural nano-catalyst provides an effective way for CO2 capture and conversion.